Uji Fisikokimia Masker Peel Off Dari Sediaan Rumput Laut (Sargassum Sp) Dan Gelatin Kulit Ikan Tuna - Putalan, Reinal; Ariany, Septian Palma; Pomolango, Lusy (Universitas Madako Tolitoli, 2024)
Peel off mask is one type of face mask that has advantages in its use, which is easy to remove or lift like an elastic membrane, which can be made from Sargassum sp seaweed with the addition of gelatin as a gel formation. This study aims to obtain the best formula for seaweed peel off masks (Sargassum sp) with the addition of tuna skin gelatin which varies as a gelling agent, by testing pH, Viscosity, Drying Preparation Time, and Antioxidant Activity. This research method uses a completely randomized design (CRD) and descriptive. The results of the tests that meet the pH values ​​at P0(7.31), P1(7.06), P2(6.83), P3(6.79), P4(6.54), P5(6.41) have according to SNI 16-4399-1996 with a range of 4.5-8.0, the value of Viscosity P5 (28893 Cps) in accordance with SNI 16-6070-1996 with a range of 2.000-50.000, the results of the long drying time test on the selected product are P4 (28 minutes) and P5 (24 minutes) the results are in accordance with the peel off mask time span, which is 5-30 minutes, and the Antioxidant Activity IC50 is 135.648 µg/ml in the medium category.